Analisis Aspek K3 serta Perancangan Ulang Tata Letak Industri Tahu di Kota Semarang “Sukses Sejatera” - Firda Aulia Nisawati; Rois Fatoni (Syntax Corporation Indonesia, 2025)
This study aims to analyze Occupational Health and Safety (OHS) aspects and redesign the layout of the